Antibacterial Activity of Bohera (Terminaliabellirica) Extract against Dental Carries Causing Bacteria Streptococcus mutans - Mizan, MRB; Kamrunnahar, -; Azad, MAK (Journal of Environmental Science and Natural Resources, 2018)
Dental caries is very common to people of Bangladesh. The treatment of dental carries is very expensive so alternative lowcost option from plant products are important for the rural people. Bohera (Terminaliabellirica) is known to people for its medicinal values. The antibacterial activity of methanolic extracts of bohera bark and fruits were tested against dental caries causing bacteria Streptococcus mutans. It was found that crude extracts of both bark and fruits of bohera have the antibacterial activity against Streptococcus mutans. The crude extract was purified with sillica gel (230-300mesh)with gradient elution of methanol, ethanol and chloroform. The purified extract of bohera also showed strong antibacterial activity against dental caries causing bacteria Streptococcus mutans. The rural people of Bangladesh may use the barks and fruits of bohera to control the dental caries problem locally. J. Environ. Sci. & Natural Resources, 10(2): 117-120 2017